2020
DOI: 10.3390/ijerph17249314
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Consumer Activity Monitors and an Algorithm Using Smartphone Data for Measuring Steps during Different Activity Types

Abstract: Background: Consumer activity monitors and smartphones have gained relevance for the assessment and promotion of physical activity. The aim of this study was to determine the concurrent validity of various consumer activity monitor models and smartphone models for measuring steps. Methods: Participants completed three activity protocols: (1) overground walking with three different speeds (comfortable, slow, fast), (2) activities of daily living (ADLs) focusing on arm movements, and (3) intermittent walking. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
(37 reference statements)
1
16
1
Order By: Relevance
“…In a recent study, Höchsmann et al [ 52 ] found that the wrist GT3X+ step count was overestimating steps especially during low, but active (e.g., public transport or car driving) or even inactive (e.g., sitting or laying) situations, when compared with ankle-based measurements (see also Figure A1 ). Thus, in principle, the differences between the MB and GT3X step counts in the current study could also be explained by an overestimation of the GT3X wrist step count in free-living conditions, which is also in line with the observation of Hartung et al [ 29 ]. Based on the current results, we therefore concluded that the MB adequately captured activity fluctuations across days, but raw absolute values were hard to compare and differed widely between actigraphy devices.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In a recent study, Höchsmann et al [ 52 ] found that the wrist GT3X+ step count was overestimating steps especially during low, but active (e.g., public transport or car driving) or even inactive (e.g., sitting or laying) situations, when compared with ankle-based measurements (see also Figure A1 ). Thus, in principle, the differences between the MB and GT3X step counts in the current study could also be explained by an overestimation of the GT3X wrist step count in free-living conditions, which is also in line with the observation of Hartung et al [ 29 ]. Based on the current results, we therefore concluded that the MB adequately captured activity fluctuations across days, but raw absolute values were hard to compare and differed widely between actigraphy devices.…”
Section: Discussionsupporting
confidence: 91%
“…Part of this disagreement could be expailned by including only 44 days of recorded data under free-living conditions in a sample of 20 participants in Degroote’s study, compared to 162 days and 21 participants analyzed in the current study (mean = 8; range: 5–13). According to Hartung et al [ 29 ], MB counted 63 out of 250 manually counted steps too few, whereas the GT3X counted even 30 steps more in a natural walking condition, confirming the general underestimation of the MB device for step counts. In a recent study, Höchsmann et al [ 52 ] found that the wrist GT3X+ step count was overestimating steps especially during low, but active (e.g., public transport or car driving) or even inactive (e.g., sitting or laying) situations, when compared with ankle-based measurements (see also Figure A1 ).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…It limits the generalizability to everyday life, where further pitfalls not addressed in this study can impact measures of step count. 47,[57][58][59] The implemented method is made available to the research community as open source. This enables further development by any party and ensures transparency and reproducibility by making decisions during data processing that impact results clear.…”
Section: Biomechanicsmentioning
confidence: 99%